Relación entre adicción al internet y autoestima en adolescentes escolares de Lima - Carbone Carrasco, Gianinna Milagros (2021)
Internet use by adolescents has risen intensely over the past decade, along with the digital risks that its problematic use entails. This has caused the internet to be associated with several psychological variables. The aim of this study is to analyse the relationship between internet addiction and self-esteem in high school adolescents from Lima Metropolitana. Participants were 3rd, 4th and 5th grade students in public and private schools in Lima (N = 154, M = 15.17, SD =1.01, 64.28% women, 35.71% men). It is a non-experimental research conducted using a cross-sectional survey and correlational design. The instruments used for this study were the Internet Addiction Test and Rosenberg Self-Esteem Scale which have been adapted to the Lima context. The results show that there is a small statistically significant negative correlation between internet addiction and self-esteem in high school adolescents in Lima. Findings also indicate evidence of statistically significant correlations between variables and their dimensions. This study calls for further research to study the causal relationship that could exist between both variables, which is still unclear.